Melville, shame, and the evil eye : a psychoanalytic reading - Adamson, Joseph, 1950- (SUNY series in psychoanalysis and culture., 1997)
This study offers a complex analysis of the psychodynamic role of shame in Melville's work, with detailed readings of Moby-Dick, Pierre, and "Billy Budd." Its concrete application of the rich analytic framework supplied by work of such theorists as Heinz Kohut, Leon Wurmser, Silvan Tomkins, and Donald Nathanson implicitly challenges the contemporary reliance on an often abstract poststructuralist model of psychoanalysis.